ARTIKEL REVIEW KASUS IMPLAN GIGI: EVALUASI PROSEDUR, TANTANGAN, DAN HASIL KLINIS - Halim, Susanna; Rusip, Gusbakti; Sinurat, Ariel Oertega (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
The use of dental implants is increasingly recognized as a solution to replace missing teeth. This research aims to explore the selection of materials and techniques in the development of effective and biocompatible dental implants. The main focus of this study is on bioactive materials such as hydroxyapatite (HA) and calcium metaphosphate (CMP), as well as the potential of hydroxyapatite from chicken bone as an alternative coating for dental implants. Additionally, the importance of public education through religious-based counseling is also explored to enhance the acceptance of this technology. The method used in this research is a literature review and analysis of relevant research findings. The studies analyzed include those on surface modification of dental implants with bioactive materials, the potential of hydroxyapatite from chicken bone, and research on public counseling regarding dental implants from an Islamic perspective. The analysis involves comparing the findings from existing studies and drawing key conclusions from each stud.. The results of the study show that surface modification of implants with bioactive materials can enhance bone healing and the success of osseointegration. The CMP coating proves to be superior to HA in terms of resistance to delamination and particle reduction, which could lead to implant failure. Surface modification of implants with bioactive materials like CMP and HA plays a significant role in improving osseointegration and implant stability. Moreover, the use of hydroxyapatite from chicken bone as an alternative coating for implants provides a cost-effective solution and has the potential to reduce the cost of dental implant development. Surface modification of implants with bioactive materials such as HA and CMP can improve osseointegration success, with CMP showing superiority. Additionally, hydroxyapatite from chicken bone offers a cost-effective solution in the development of dental implants. ABSTRAKPenggunaan implan gigi semakin berkembang sebagai solusi untuk menggantikan gigi yang hilang. Penelitian ini bertujuan untuk mengeksplorasi pemilihan bahan dan teknik dalam pengembangan implan gigi yang efektif dan biokompatibel. Fokus utama penelitian ini adalah bahan bioaktif seperti hydroxyapatite (HA) dan calcium metaphosphate (CMP), serta potensi hidroksiapatit dari tulang ayam sebagai alternatif pelapis implan gigi. Selain itu, pentingnya edukasi masyarakat melalui penyuluhan berbasis agama juga dieksplorasi untuk meningkatkan penerimaan teknologi ini. Metode yang digunakan dalam penelitian ini adalah tinjauan literatur dan analisis hasil penelitian terkait. Penelitian yang dianalisis meliputi studi tentang modifikasi permukaan implan gigi dengan bahan bioaktif, potensi hidroksiapatit dari tulang ayam, dan penelitian tentang penyuluhan masyarakat mengenai implan gigi dalam perspektif Islam. Analisis dilakukan dengan membandingkan hasil penelitian yang ada dan menyimpulkan temuan utama dari masing-masing studi. Hasil penelitian menunjukkan bahwa modifikasi permukaan implan dengan bahan bioaktif dapat meningkatkan penyembuhan tulang dan keberhasilan oseointegrasi. Lapisan CMP terbukti lebih unggul dibandingkan HA dalam ketahanan terhadap delaminasi dan pengurangan partikel yang dapat menyebabkan kegagalan implan. Modifikasi permukaan implan dengan bahan bioaktif seperti CMP dan HA memberikan kontribusi penting dalam meningkatkan osseointegrasi dan stabilitas implan. Selain itu, penggunaan hidroksiapatit dari tulang ayam sebagai alternatif pelapis implan memberikan solusi biaya efektif dan berpotensi mengurangi biaya pengembangan implan gigi. Modifikasi permukaan implan dengan bahan bioaktif seperti HA dan CMP dapat meningkatkan keberhasilan oseointegrasi, dengan CMP menunjukkan keunggulan. Selain itu, hidroksiapatit dari tulang ayam menawarkan solusi biaya efektif dalam pengembangan implan gigi.